The disinterested government: An interpretation of China's economic success in the reform era - Yang Yao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
In the last 30 years, China has achieved high economic growth and successfully transformed its economy from a planned economy to a market-based system. The country, to a large extent, has attained success through the recommendations proposed by standard economic theory. However, the role of political economy has been omitted from the literature: how did China adopt the right economic policies and the appropriate road to reform? This paper attempts to answer this question. The central assumption of the paper is that China achieved success because the Chinese government has been a disinterested party, i.e., a government that does not favour any particular sections of the population and prioritizes the long-term welfare of the whole society. In this paper, we first define and analyse the concept of disinterested governments, and then proceed to provide several examples to demonstrate that China has been characterized by a disinterested government. Based on a theoretical model, we also discuss the reasons of the Chinese government becoming a disinterested government.
Keywords: O43; O53; D73; 330; disinterested governments; the China miracle; economic reform